Intervalwise block partitioning for 3-point in solving linear systems of first order ordinary differential equations - Mahayadin, Mahfuzah; Othman, Khairil Iskandar; Ibrahim, Zarina Bibi (AIP Publishing, 2016)
Intervalwise partitioning is a strategy to solve stiff ordinary differential equations (ODEs). This strategy using on 3-point block method will initially starts solving ODE using Adams method, and switch the system to Backward Differentiation Formula (BDF) when there is an indication of stiffness. Indication of stiffness will be based on hacc > hiter and the trace of the Jacobian. The comparison with existing method reveals that this partitioning strategy can be an alternative method to solve stiff ODEs.